Pseudosubstrate regulation of the SCF(β-TrCP) ubiquitin ligase by hnRNP-U - Davis, Matti (Cold Spring Harbor Laboratory Press, 2002)
β-TrCP/E3RS (E3RS) is the F-box protein that functions as the receptor subunit of the SCF(β-TrCP) ubiquitin ligase (E3). Surprisingly, although its two recognized substrates, IκBα and β-catenin, are present in the cytoplasm, we have found that E3RS is located predominantly in the nucleus. Here we report the isolation of the major E3RS-associated protein, hnRNP-U, an abundant nuclear phosphoprotein. This protein occupies E3RS in a specific and stoichiometric manner, stabilizes the E3 component, and is likely responsible for its nuclear localization. hnRNP-U binding was abolished by competition with a pIκBα peptide, or by a specific point mutation in the E3RS WD region, indicating an E3–substrate-type interaction. However, unlike pIκBα, which is targeted by SCF(β-TrCP) for degradation, the E3-bound hnRNP-U is stable and is, therefore, a pseudosubstrate. Consequently, hnRNP-U engages a highly neddylated active SCF(β-TrCP), which dissociates in the presence of a high-affinity substrate, resulting in ubiquitination of the latter. Our study points to a novel regulatory mechanism, which secures the localization, stability, substrate binding threshold, and efficacy of a specific protein-ubiquitin ligase.